Suicide in professional American football players in the past 95 years. (5th December 2016) - Webner, David; Iverson, Grant L.
Abstract: Objective : To examine publicly-available information on all identified cases of suicide in active or former American professional football players between 1920 and the spring of 2015. Design : Retrospective cohort study. Setting : Professional American Football in the US. Participants : A cohort of 26 702 athletes who had died, retired or were currently playing in the NFL from nfl.com since 1920 was identified. Main outcome measures : Internet queries identifying 26 professional football players who completed suicide. Obituaries and news reports were reviewed. The primary outcome measures included mortality, demographic characteristics and life circumstances in professional American football players completing suicide. Results : From 1920–2015, the median age of the 26 men who completed suicide was 39.5 years (range = 23–85). The median number of years after retirement was 6.5 (range = 0–63). Most of the deaths since 1920 have occurred in the past 15 years (58.7%) and a large percentage have occurred since 2009 (42.3%). Most of the men suffered from multiple life stressors prior to their deaths, such as retirement from sport, loss of steady income, divorce, failed business ventures, estrangement from family members and medical, psychiatric and/or substance abuse problems. Conclusions : A disproportionate number of completed suicides in current and former professional football players have occurred since 2009 (42.3%). It is well established in the literature that the causes of depression and suicidality are diverse, often multifactorial and treatable. Providing at-risk retired athletes with mental health treatment will likely reduce their suffering and improve their quality-of-life.